Distinct immune responses in people living with HIV following SARS-CoV-2 recovery - Dieter Mielke; Shuying Sue Li; Daniel J. Schuster; Xiaohong Li; Jiani Hu; Shelly Karuna; Kelly E. Seaton; Caroline Brackett; Brooke Dunn; Taylor Keyes; Adam Zalaquett; Sherry Stanfield-Oakley; et al. (Communications Medicine)
Abstract Background SARS-CoV-2 infection results in greater disease severity among immunocompromised individuals compared to healthy individuals. However, there is conflicting information about the impact of chronic HIV infection on immune responses to SARS-CoV-2 infection and vaccination. Method We used a combination of machine learning approaches and network analysis to explore 56 immune markers and comprehensively profile humoral and cellular immunity in a cross-sectional observational cohort of people without HIV (PWOH; n = 216) and people living with HIV (PLWH; n = 43) who recovered from SARS-CoV-2 infection (13–131 days since SARS-COV-2 diagnosis) early in the pandemic. Results PLWH recovered from symptomatic outpatient COVID-19 exhibit lower humoral and B cell responses to SARS-CoV-2 vs. PWOH but, surprisingly, both symptomatic outpatient and hospitalized PLWH have higher anti-endemic coronavirus antibody responses compared to PWOH counterparts and asymptomatic PLWH. The latter observation suggests that this was not strictly due to broadly elevated levels of anti-endemic coronavirus antibodies in PLWH. Moreover, correlation-based analysis reveals that while different compartments of the immune response to SARS-CoV-2 infection are positively correlated in PWOH recovered from symptomatic outpatient COVID-19, these correlations are weaker in PLWH. Conclusion Our analyses reveal significant differences in the coordinated immune responses elicited by infection in PLWH compared to PWOH.